ROLE OF FREE SOLUBLE VASCULAR ENDOTHELIAL GROWTH FACTOR-A (VEGF-A) IN PRE-ECLAMPSIA. - DR. MUNMUN DAS(SARKAR); DR. TAPAN KUMAR GHOSH (International Journal of Pharma and Bio Sciences, 2013)
Hypertension is one of the common medical disorders of pregnancy and is reported to complicate up to 1 in 10 gestations. Altered utero-placental blood flow has long been the focus of the pathophysiology of preeclampsia. Vascular endothelial growth factor (VEGF) may be important in mediating the endothelial response that occurs in preeclampsia. The pathophysiology of preeclampsia remains largely undiscovered. In this back ground the present study was conducted with the following objects. To determine whether altered levels of active vascular endothelial growth factor may be implicated in the pathogenesis of preeclampsia, and whether VEGF mediates the endothelial cell activation that is involved in the pathogenesis of the clinical syndrome